Analysis of the Gema Madani Program as a Participatory Public Policy in the City of Tasikmalaya - Sundawa Bahtiar (Jurnal Mantik, 2022)
The Tasikmalaya City Government has basically issued a policy on the Mayor of Tasikmalaya regulation number 8 of 2016 concerning guidelines for implementing the Civil Society Movement program, which is competitive and innovative, this program comes from the Tasikmalaya City Budget by distributing funds for the development of various infrastructures and also improving the quality of human resources. In a competitive environment, in the process the Gema Madani program in the City of Tasikmalaya has been implemented well by each Kelurahan in its area, however, there are some shortcomings that still need to be improved, especially in terms of its implementation to the whole community. This research is a type of qualitative research, using descriptive methods, while the purpose of this study is to analyze the Gema Madani program as a participatory public policy in the City of Tasikmalaya, and the results of this study explain that, the City Government of Tasikmalaya in its efforts to increase public participation In development, and as an effort to prosper the underprivileged, the Gema Madani Program (Independent and Innovative Community Movement) was launched, where the program was built on several considerations such as increasing regional economic capacity, labor quality, agriculture and regional food security. Through the echo Madani program, namely the Independent, Competitive and Innovative Community Movement, the City of Tasikmalaya government is expected to be able to strengthen the capacity of community development in the context of developing regional autonomy. There are several factors that still need to be a concern for policy makers, namely in determining human resources as policy implementers, it takes people who have knowledge and abilities in various programs planned through the Madani Overtime program in order to run efficiently and effectively